2015
DOI: 10.1073/pnas.1510749112
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticography reveals the temporal dynamics of posterior parietal cortical activity during recognition memory decisions

Abstract: Theories of the neurobiology of episodic memory predominantly focus on the contributions of medial temporal lobe structures, based on extensive lesion, electrophysiological, and imaging evidence. Against this backdrop, functional neuroimaging data have unexpectedly implicated left posterior parietal cortex (PPC) in episodic retrieval, revealing distinct activation patterns in PPC subregions as humans make memory-related decisions. To date, theorizing about the functional contributions of PPC has been hampered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 54 publications
9
64
2
Order By: Relevance
“…The low and high gamma effects were localized to the left posterior parietal cortex and the left inferior frontal-temporal cortex, respectively. In conjunction with these source localization results and previous literature, Nieuwland and Martin (2017) interpreted the low gamma effect as reflecting referent activation by the brain's recognition memory network (Gonzalez et al, 2015;Wagner, Shannon, Kahn, & Buckner, 2005), while the high gamma effect was taken to reflect integration with the sentence context (Bastiaansen & Hagoort, 2015;Fedorenko et al, 2016;Peña & Melloni, 2012). Nieuwland and Martin (2017) did not observe modulations in the theta range, but suggested that theta effects may occur in a comparison of old and new referents.…”
Section: Oscillatory Correlates Of Referent Activation and Integrationsupporting
confidence: 68%
“…The low and high gamma effects were localized to the left posterior parietal cortex and the left inferior frontal-temporal cortex, respectively. In conjunction with these source localization results and previous literature, Nieuwland and Martin (2017) interpreted the low gamma effect as reflecting referent activation by the brain's recognition memory network (Gonzalez et al, 2015;Wagner, Shannon, Kahn, & Buckner, 2005), while the high gamma effect was taken to reflect integration with the sentence context (Bastiaansen & Hagoort, 2015;Fedorenko et al, 2016;Peña & Melloni, 2012). Nieuwland and Martin (2017) did not observe modulations in the theta range, but suggested that theta effects may occur in a comparison of old and new referents.…”
Section: Oscillatory Correlates Of Referent Activation and Integrationsupporting
confidence: 68%
“…101 ). Recently, an electrocorticography study 102 reported greater sustained high-frequency gamma power, a proxy signal for multiunit activity, for old versus new correct decisions in the IPS; this increase in gamma power decayed only 200 ms before the motor response, consistent with an accumulator hypothesis.…”
Section: Decision Making and Motor Intentionmentioning
confidence: 81%
“…In addition, several aspects of these experiments suggest caution in over-generalizing these results. First, because of limitations in the sampling rate of the behavioral output (behavioral flags were determined manually on the clinical video --30 fps), we did not attempt to evaluate effects that occurred at frequencies greater than 30 Hz, which are likely functionally significant [7,[27][28][29]. Second, brain coverage with electrodes was dictated by clinical necessity.…”
Section: Figurementioning
confidence: 99%